Biohydrogen production from diluted-acid hydrolysate of rice straw in a continuous anaerobic packed bed biofilm reactor. (29th January 2022) - Safari, Mohammad; Tondro, Hadiseh; Zilouei, Hamid
Abstract: Bio-hydrogen production in a continuously operated anaerobic packed bed biofilm reactor (APBR) using acid-hydrolysate of rice straw as feedstock and inoculated with an anaerobic mesophilic sludge from a municipal wastewater treatment plant was investigated at three different HRTs (17, 8.2 and 2 h). Fermentable sugars solution achieved from a two-stage diluted acid hydrolysis of rice straw was used as the feedstock. First, rice straw was treated with 1% w v −1 sulfuric acid at 120 °C for 30 min with a yield of 58.5% xylose. Higher temperature of 180 °C for 10 min at 0.5% w v −1 sulfuric acid was applied in the second stage in which cellulosic crystalline structure was partially depolymerized to glucose with a yield of 19.3% glucose. Hydrogen production rate and yield were enhanced as the hydraulic retention time was decreased with a maximum production rate of 252 mL L −1 h −1 and yield of 1 mol H2 mol −1 sugar consumed at 2 h HRT. Experimental results illustrated the increase of COD conversion from 44% to 47% by shortening the HRT from 17 to 2 h. Furthermore, acetic acid and butyric acid production were reduced slower than other soluble metabolites like ethanol. Graphical abstract: Image 1 Highlights: Decrease of HRT favors H2 production performance due to higher hydrogen-producing bacteria activity. Yield and rate of H2 were 1.0 mol mol −1 sugar and 252 mL L −1 h −1 at 2 h HRT. Decrease of HRT reduced sugar conversion from 77% to 68.9% at 2 h HRT. Decrease of HRT reduced SMP concentration from 1169 mg L −1 to 897 mg L −1 at 2 h HRT. Decrease of HRT reduced the TCOD mass balance from 62% to 59% at 2 h HRT.